ANALISIS PENGARUH PERTUMBUHAN EKONOMI DAN INVESTASI TERHADAP PENGANGGURAN DAN KEMISKINAN DI KABUPATEN/KOTA PROVINSI BALI - Sudarsana Arka, I Ketut Gede Pande Supriawan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Economic growth, investment, unemployment and poverty are interrelated. It is difficult for the government to create new jobs without economic growth, so the unemployment rate will also increase. Poverty has become a major concern in the development of social policy. The purpose of this study was to analyze the effect of economic growth and investment on unemployment and poverty in Bali Province districts/cities in 2009-2015. Based on the results of the analysis it was found that; (i) Economic growth and direct investment do not have a significant effect on unemployment in the districts/cities of Bali Province. (ii) Economic growth and investment directly have a negative and significant effect on poverty in Bali's districts/cities. The policy steps that need to be taken also to overcome the problem of unemployment and poverty in the regencies/cities of Bali Province, by way of; improving the quality of human resources through work education and training so as to create quality workforce, expanding employment opportunities in the country and abroad, as well as mapping the workforce potential in all districts/cities of the Province of Bali must be in accordance with their abilities and expertise.